2019
DOI: 10.1080/0886022x.2019.1655450
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of Nrf2 accelerates renal lipid deposition through suppressing the ACSL1 expression in obesity-related nephropathy

Abstract: Background: Obesity has become a worldwide epidemic, and the incidence of obesity is increasing year by year. Obesity-related nephropathy (ORN) is a common kidney complication of obesity. Long-chain acyl-CoA synthetases-1, (ACSL1), is a key enzyme in the oxidative metabolism of fatty acids in mitochondria and ACSL1 may play a direct role in renal lipid deposition and promote the progress of ORN. In this study, we focus on the renoprotective role of ACSL1 in ORN.Methods: Electron microscopy, immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The main saturated fatty acids, such as PA, has shown contributions to renal damage through increasing excessive ROS generation, apoptosis and endoplasmic reticulum (ER) stress [34,35]. In our previous studies, obvious renal lipid deposition and tubules damages were found in PA-induced HK-2 cells and T2DM rats [33,36]. In this study, we found that, with the prolongation of PA exposure, the cells viability was signi cantly decreased, and the apoptosis and lipids deposition were also signi cantly increased in HK-2 cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The main saturated fatty acids, such as PA, has shown contributions to renal damage through increasing excessive ROS generation, apoptosis and endoplasmic reticulum (ER) stress [34,35]. In our previous studies, obvious renal lipid deposition and tubules damages were found in PA-induced HK-2 cells and T2DM rats [33,36]. In this study, we found that, with the prolongation of PA exposure, the cells viability was signi cantly decreased, and the apoptosis and lipids deposition were also signi cantly increased in HK-2 cells.…”
Section: Discussionmentioning
confidence: 95%
“…When the body's lipids are overloaded, the lipid balance is disrupted, leading to lipid metabolism system unable to proceed normally and cause lipotoxicity [31,32]. It has been reported that cellular lipotoxicity contributes to obesity-related nephropathy [33]. The main saturated fatty acids, such as PA, has shown contributions to renal damage through increasing excessive ROS generation, apoptosis and endoplasmic reticulum (ER) stress [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Mammal studies showed that the ACSL1-6 are essential enzymes for the utilization of cellular LCFAs, which is the first enzyme to activate LCFAs, and determines their metabolic fate, including fatty acid β -oxidation, lipogenesis and signal lipids [ 2 , 20 ]. For example, ACSL1 and ACSL5 tend to be involved in fatty acids β -oxidation [ 21 , 22 ]. ACSL3 and ACSL4 mediate the lipid synthesis and lipid droplets biogenesis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipids are the fundamental composition of cells. They present in the kidneys include triglycerides, phospholipids, cholesterol and its esters, and free fatty acids (FFAs; Hagve et al, 2001 ; Herman-Edelstein et al, 2014 ; Chen et al, 2019 ). In mammalian cells, FFAs are generated through the de novo synthetic pathway and released when triglycerides and phospholipids are hydrolyzed by cellular lipases ( Schaffer, 2003 ).…”
Section: Role Of Lipids In Renal Proximal Tubular Physiological Functionmentioning
confidence: 99%